Analisis dan Uji Kekuatan Pukul Komposit Helm Ukuran Dewasa berbasis Ijuk Resin dengan Perendaman Alkali - Santoso, Satria Ageng Gigih; Hadi, Syamsul; Firdaus, Prima Rifqi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Indonesia is one of the countries with abundant availability of palm fiber composite, yet its application in advanced material technology remains limited. On the other hand, most motorcycle helmets available in the market are made from ABS plastic, which has limitations in impact energy absorption and may increase the risk of head injuries during accidents. This study aims to develop helmet composites based on palm fiber and epoxy resin by varying the fiber volume fractions (15%, 25%, and 35%) and alkali soaking durations (75, 150, 225, and 300 minutes). The impact strength test results showed that the combination of 35% fiber volume and 225-minute alkali soaking produced the highest specific impact energy (SIP) of 0.142 J/mm². As a comparison, SNI-compliant helmets made from ABS plastic only reached an EPS value of 0.00972 J/mm², indicating that palm fiber-based composite helmets could improve impact energy absorption efficiency by more than 14 times. The results conclude that increasing the fiber volume fraction and optimizing the alkali treatment duration significantly enhances the impact resistance, making ijuk-based composite helmets a promising alternative for safer and more eco-friendly protective gear.